Representações de saúde-doença e alternativas terapêuticas em bairros da periferia de Belo Horizonte (1994-1996) - Clara de Jesus Marques Andrade (1996)
This paper is a result of a field research based on quality data, done with the inhabitants of the Solimões and Conjunto Jardim Felicidade neighborhoods, in the metropolitan area of Belo Horizonte-MG, with the goal of identifying the representations in the process health-sisckness and therapeutic alternatives. The option for its execution was to do a participative observation, semi-strutured interviews and analise of interviews, according to the proposed methodology of BARDIN (1977), TRIVIÑOS (1987) and MINAYO (1993). The participative observation has been done since 1986, trough the development of a extension project of the official local health services and participation in neighborhood-organized activities and meetings. The interviews, that lasted approximately 60 minutes, were done from November, 1994 to July, 1995 with thirty women whose ages vary from 18 to 40 years, all of them with children between 0and 5 years old. Besides, two women above the age of 60 offered to colaborate on the reserach. Trough the analises of the interviews the categories of representation of the process health-sickness were reached. Sickness is represented as funcional and useful disablement of the body. Health, besides being represented as the contrary of sickness, in other words, a funcional and uswful body, has yet many other representations, such as: a health lifestyle, quality medical assistence, and yet balance and harmony in the relations with nature and God. This study shows that these representations are strickly